How does the energy from renewable sources change the price of electricity on the wholesale market? - Albrechtová, Aneta; Mirvald, Michal; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
This bachelor's thesis investigate how electricity from renewable energy sources changes the price of electricity on wholesale market. I used data from the Germany in the year 2013 and because of high correlation between the Czech and the German wholesale price of electricity. Therefore I assume that the same effect operate also in the Czech Republic. By using a regression analysis, I prove that an increase in the RES, precisely wind and photovoltaic, electricity production does significantly lowers the price of electricity on wholesale market. Results show that size of consumption, prise of gas and price of allowances have a significant impact on wholesale price.
Vedoucí práce: Michal Mirvald
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses